Differential Regenerative Capacity of the Optic Tectum of Adult Medaka and Zebrafish - Shimizu, Yuki; Kawasaki, Takashi (Frontiers in Cell and Developmental Biology, 2021)
Zebrafish have superior regenerative capacity in the central nervous system compared to mammals. In contrast, medaka were shown to have low regenerative capacity in the adult heart and larval retina, despite the well-documented high tissue regenerative ability of teleosts. Nevertheless, medaka and zebrafish share similar brain structures and biological features to those of mammals. Hence, this study aimed to compare the neural stem cell responses and regenerative capacity in the optic tectum of adult medaka and zebrafish after stab wound injury. Limited neuronal differentiation was observed in the injured medaka, though the proliferation of radial glia was induced in response to tectum injury. Moreover, the expression of the pro-regenerative transcriptional factors ascl1a and oct4 was not enhanced in the injured medaka, unlike in zebrafish, whereas expression of sox2 and stat3 was upregulated in both fish models. Of note, glial scar-like structures composed of GFAP+ radial fibers were observed in the injured area of medaka at 14 days post injury. Altogether, these findings suggest that the adult medaka brain has low regenerative capacity with limited neuronal generation and scar formation. Hence, medaka represent an attractive model for investigating and evaluating critical factors for brain regeneration.